Somatism "Heart" in German and Thai Idioms: A cognitive-semantic Analysis - Huaihongtong, Supattra (Nusantara Science and Technology Proceedings)
This article examines the cognitive-semantic comparison to semantic structuring of heart in German and Thai idioms based on the metaphor. In order to achieve this goal, the idioms are investigated with the aid of the cognitive metaphor theory of Lakoff and Johnson. The result shows that the heart in German and Thai idioms conveys the meaning of feeling, thought, character, desire, etc., by itself. While structuring the specific meanings, e.g. sadness, love, etc., the metaphor plays an important role.